Peningkatan Kadar Imunosupresan IDO (Indoleamin 2,3-dioksigenase) pada Supernatan Kultur Sel Punca Mesenkim yang Distimulasi dengan Agregat Imunoglobulin G - DIAN RATIH LAKSMITAWATI; JEANNE ADIWINATA PAWITAN; MOHAMAD SADIKIN; CAROLINE TAN SARDJONO (Fakultas Farmasi Universitas Pancasila, 2014)
Mesenchymal stem cells have been known to have the nature of supressing immune response. This cell have been proven to reduce the symptoms of organ transplants rejection. Clinically proofing is also being performed on an autoimmune disease caused by the complex immune such as systemic lupus erythematosus (SLE). This study aimed to know aggregated IgG-stimulating effects of mesenchymal stem cells in relation to IDO secretion, an immunosuppressant agent. Mesenchymal stem cells was isolated from liposuction waste and characterized based on its surface molecule accrording to ISCT criterias. The confirmed cell culture was used to the next culture by the addition of heat aggragated immunoglobulins gamma (HAGG) for six days. IDO secreted on supernatant culture was collected and assayed by elisa method at 450 nm. The results showed that there was elevated levels of IDO (16.73-49.5%) on culture with HAGG stimulation than without stimulation. This study could be a part of the basic